2010
DOI: 10.1007/s12613-010-0337-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of isothermal aging on σ precipitation in super duplex stainless steel

Abstract: The time-temperature-transformation (TTT) curve of the 00Cr25Ni7Mo4N duplex stainless steel was obtained with a Formastor-digital thermal dilatometer, and the influence of isothermal aging on σ precipitation was studied by metallographic observation, X-ray diffraction (XRD), and transmission electron microscopy (TEM). The results show that the decomposition of ferrite phase is accompanied by the formation of σ phase at 750-1000°C, especially in the range of 800-900°C. The longer the aging time, the higher the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Figure 2b shows the microstructure for specimen (S-5), which was subjected to an isothermal treatment at 900°C for 5 minutes. During this time, the microstructure did not undergo signi cant transformations, such as the presence of deleterious phases, which is in agreement with the response found in the TTT diagram in the work of [37]. The precipitation of deleterious phases and other changes are seen in specimen (S-15) as shown in Fig.…”
Section: Microstructure Analysissupporting
confidence: 87%
“…Figure 2b shows the microstructure for specimen (S-5), which was subjected to an isothermal treatment at 900°C for 5 minutes. During this time, the microstructure did not undergo signi cant transformations, such as the presence of deleterious phases, which is in agreement with the response found in the TTT diagram in the work of [37]. The precipitation of deleterious phases and other changes are seen in specimen (S-15) as shown in Fig.…”
Section: Microstructure Analysissupporting
confidence: 87%
“…In the case of welding, not every phase or precipitation needs to be considered, since several phases, such as, for example, the σ phase, need more time to form than is available during welding [17,18].…”
Section: Microstructure Of Duplex Stainless Steelsmentioning
confidence: 99%
“…The σ phase is hard and brittle, and it is the most harmful precipitation phase in steel, which can significantly reduce the plasticity of steel [6][7][8][9]. Amit [7] and Wang [10] et al believed that it is the slow cooling rate during forging that transforms δ phase to σ phase, and the precipitation of σ phase in this process damages the hot workability. It was observed that the high content of α-phase stabilising elements in SAF3207, such as Cr, Mo, and Ni, can promote the precipitation of σ phase, making the hot workability problems more typical [4,11].…”
Section: Introductionmentioning
confidence: 99%